Bioluminescence probe for γ-glutamyl transpeptidase detection in vivo. Issue 1 (1st January 2018) - Lin, Yuxing; Gao, Yuqi; Ma, Zhao; Jiang, Tianyu; Zhou, Xin; Li, Zhenzhen; Qin, Xiaojun; Huang, Yun; Du, Lupei; Li, Minyong
Graphical abstract: Abstract: To detect γ-Glutamyl Transpeptidase (GGT) activity in vitro and in vivo, a bioluminescence probe with high sensitivity and specificity was well designed and synthesized. This probe can be recognized by GGT and release strong bioluminescence with its further reaction with luciferase. The performance of this probe was demonstrated in vitro and in cells. Finally, we applied the probe for detection of GGT activity in xenograft model.